Modification of The Front Kick Accuracy for Pencak Silat Novice Athletes (Universitas Negeri Semarang, 2022)
The purpose of this study was to create a media for front kick accuracy in Pencak silat athletes. This type of this study is research and development (RD) with descriptive data analysis techniques using percentages. The instrument used was a questionnaire. The result of this research is a modified front kick precision tool. This study found that the expert validation data is 98.75% in the